Second harmonic generation of optical spin−orbit interactions in hybrid plasmonic nanocircuits - Shi Junjun; Jing Kangcheng; Li Li; Zhang Wenjun; Zhang Tianzhu; He Xiaobo (Nanophotonics)
The manipulation of nonlinear spin–orbit interaction at the nanoscale is crucial for advancing information processing in integrated nanophotonics. However, the weak spin–orbit interaction (SOI) in conventional waveguide materials significantly limits the efficiency of nonlinear optical processes. In this work, we design a hybrid plasmonic waveguide composed of a gold film and a Y-branch CdSe nanowire, which addresses the aforementioned limitations. The designed hybrid structure enables efficient directional emission of second-harmonic generation (SHG) via control of the polarization of the excitation light. The transversely emitted SHG can be visualized for directly imaging the SOI. Our work not only provides a way to enhances the efficiency of the nonlinear SOI but also a promising platform for further advances in integrated photonics and nonlinear optics.